Novel Molecular Approaches to Target Microbial Virulence - Holban, Alina Maria (De Gruyter, 2015)
Microbial infections still represent one of the major causes of mortality and morbidity worldwide. Irrational usage of antimicrobials has lead to increased resistance, causing clinical, social and economical disabilities. Therefore, one of the major challenges of scientists is to develop novel alternative methods to handle infections and reduce resistance and other side effects produced by the actual therapies. The aim of this book is to offer a perspective on novel approaches to handle infections by using naturally-derived products in order to modulate the virulence of pathogens, without the risk of developing resistance. We intend to highlight the utility of microbial, vegetal and animal-derived compounds with potential antimicrobial activity by exploiting their effect on microbial virulence. Furthermore, this book aims to reveal the potential to assimilate recent bio-technological findings, like the usage of nanotechnology as efficient shuttles for stabilizing, improved targeting and the controlled release of natural products in order to efficiently fight infections.